Cerminan Asas Rechtssicherheit Terhadap Peralihan Hak Tanah Pertanian Absentee Akibat Dari Pewarisan Dalam Prinsip Reforma Agraria - Dewi, Ni Kade Ayu Trisna; Suyatna, I Nyoman (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 9 No 02 (2024)DO - 10.24843/10.24843/AC.2024.v09.i02.p 14, 2024)
The purpose of this research article is to examine and understand legal protection for heirs who receive absentee agricultural land from the perspective of the principle of rechtssicherheit in the principles of agrarian reform. In writing this research, normative legal research methods were used, supported by legislative approaches, analytical approaches and conceptual approaches. The results of this research show that absentee land ownership from inheritance is legal and recognized by the state because the transfer of ownership rights to heirs is a reflection of the nature of separate property rights based on Article 20 paragraph (1), namely hereditary. Regulations prohibiting absentee land ownership, as regulated in Article 3 paragraph (1) of Government Regulation no. 224 of 1961 concerning the Implementation of Land Distribution and Provision of Compensation, can give rise to legal uncertainty and is contrary to Article 28H of the 1945 Constitution which guarantees the right of every person to own land which must not be taken arbitrarily. And even though this regulation is intended for more effective land regulation, the provisions regarding the prohibition on absentee land ownership cannot immediately be enforced and must be harmonized with compensation resulting from the necessity of transferring rights to absentee agricultural land as regulated in Article 6 and Article 7 Government Regulation no. 224 of 1961.